The phosphoinositide 3-kinase Vps34p is required for pexophagy in Saccharomyces cerevisiae - Grunau, Silke Dora; Lay, Dorothee; Mindthoff, Sabrina; Platta, Harald W.; Girzalsky, Wolfgang; Just, Wilhelm W.; Erdmann, Ralf (Biochemical journal, 2011)
PIds (phosphoinositides) are phosphorylated derivatives of the membrane phospholipid PtdIns that have emerged as key regulators of many aspects of cellular physiology. We have discovered a PtdIns3P-synthesizing activity in peroxisomes of Saccharomyces cerevisiae and have demonstrated that the lipid kinase Vps34p is already associated with peroxisomes during biogenesis. However, although Vps34 is required, it is not essential for optimal peroxisome biogenesis. The function of Vps34p-containing complex I as well as a subset of PtdIns3P-binding proteins proved to be mandatory for the regulated degradation of peroxisomes. This demonstrates that PtdIns3P-mediated signalling is required for pexophagy.